Characteristics of risk factors for development of melanocytic naevi and melanoma in patients presented to a dermatologist to assess melanocytic lesions - Góralska, Agnieszka; Błaszczyk, Jan (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction . Melanocytic naevi are common in the population, and they present a diagnostic problem and can be a precursor of melanoma (MM). Risk factors for the development of melanocytic naevi are similar to melanoma. These include genetic predisposition, age, sex, the effect of hormones, exposure to ultraviolet radiation, skin phototype, latitude, social behavior, hobbies associated with exposure to the sun, and immunosuppression. Many studies have shown the impact of these factors on the initiation of the process of melano- and carcinogenesis and confirmed their cumulative effect on the incidence of melanoma. Objective . Assessment of risk factors for cutaneous melanocytic moles and melanoma in patients presenting to a dermatologist for control of melanocytic lesions and assessment of patients’ knowledge of these factors. Material and methods . In the study 99 patients (38 men and 61 women) aged 15-55 years were included. They were divided into two groups: group I (29-51 years of age – 50 patients) and group II (15-28 years of age – 49 patients). For assessment of the presence of melanocytic naevi and melanoma risk factors a personal questionnaire was used. The obtained data were subjected to qualitative and quantitative analysis, and evaluated in a test of independence (χ 2 ). Results . 50% of respondents had skin phototype 3. A high percentage of them had phototype 2 or 4, while one out of twenty tested was characterized by phototype 1. In more than 46% of patients the number of melanocyte naevi assessed by dermatologist corresponded to the number evaluated by patients. Patients were worried the most often by brown cellular naevi (30%), then by flat, dark, multi-colored naevi (29%). 52.5% of patients declared that in the last 2-5 years new melanocytic lesions had appeared, more frequently in group I (p 0.05), and the study confirmed that patients regularly spending their vacation in a hot zone more often recorded the appearance of new pigmented moles in the last 2-5 years (p < 0.05). 76% of patients declared that they definitely did not avoid sun exposure. UV sunscreen was applied by 81% of the respondents, 68.8% of patients used sunscreen once a day. The solarium was occasionally attended by 10% of the respondents. Chi-square test showed no relationship between attending a solarium and the number of moles and the development of new naevi in the last 2-5 years. Conclusions . The study population had multiple risk factors for the development of melanocytic naevi and melanoma. There is a constant need of education of patients about which lesions and which life style factors may affect the development of melanoma and atypical moles.